INTEGRATION OF EDUCATION AND SCIENCE OF UKRAINE IN CIVIL SOCIETY: SOCIAL AND PROFESSIONAL ORIENTATION - Piddiachyi, Mykola (Continuing Professional Education: Theory and Practice, 2019)
Civil society should be guided by national interests, realizing the impact of globalization on world aggregate of people united by certain relationships, due to historically variable mode of production of material and spiritual wealth. In the process of providing living space self-contained society, develop education and science; will form patriotic attitudes and beliefs; systematically use modern technologies and develop new targeted; cradle and develop the personality of a set of formal logic, language, content and aesthetic and methodological knowledge and skills that will be demonstrated in intellectual activity; attract the younger generation to work for their development; will socialize responsible for his actions competent person trained to think logically and self-development, self-education and self, able to enjoy authentic information space and to take appropriate on the basis of progressive solutions, changing lives. Socio-professional training component of the individual and society to live and work in a globalized, competitive space solves the contradiction between: social order quality training personality and insufficient preparation for its real social and professional interaction; amount of information and technology in terms fast-changinglife processes and non-adaptation of educational infrastructure towards social and professional development of the individual stages at the age of. In this article grounded: socio-professional orientation of the individual competitive in the labor market in terms of rapidly changing globalized environment of living space in the context of integration of education and science of Ukraine into space of civil society; cultural foundation of social and professional orientation; the need to design multifaceted human living space to form its psychological experience; variable nature of the content components socio-professional orientation and training requirements for individual stages of age development; approaches to shaping educational content and organization of educational process in educational institutions.